Soluble thrombomodulin protects ischemic kidneys - Sharfuddin, Asif A; Sandoval, Ruben M; Berg, David T; McDougal, Grant E; Campos, Silvia B; Phillips, Carrie L; Jones, Bryan E; Gupta, Akanksha; Grinnell, Brian W; Molitoris, Bruce A (Journal of the American Society of Nephrology, 2009)
Altered coagulation and inflammation contribute to the pathogenesis of ischemic renal injury. Thrombomodulin is a necessary factor in the anticoagulant protein C pathway and has inherent anti-inflammatory properties. We studied the effect of soluble thrombomodulin (sTM) in a hypoperfusion model of ischemic kidney injury. To markedly reduce infrarenal aortic blood flow and femoral arterial pressures, we clamped the suprarenal aorta of rats, occluding them 90%, for 60 min. Reversible acute kidney injury (AKI) occurred at 24 h in rats subjected to hypoperfusion. Histologic analysis at 24 h revealed acute tubular necrosis (ATN), and intravital two-photon microscopy showed flow abnormalities in the microvasculature and defects of endothelial permeability. Pretreatment with rat sTM markedly reduced both I-R-induced renal dysfunction and tubular histologic injury scores. sTM also significantly improved microvascular erythrocyte flow rates, reduced microvascular endothelial leukocyte rolling and attachment, and minimized endothelial permeability to infused fluorescence dextrans, assessed by intravital quantitative multiphoton microscopy. Furthermore, sTM administered 2 h after reperfusion protected against ischemia-induced renal dysfunction at 24 h and improved survival. By using an sTM variant, we also determined that the protective effects of sTM were independent of its ability to generate activated protein C. These data suggest that sTM may have therapeutic potential for ischemic AKI.